2009
DOI: 10.1063/1.3202438
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for the treatment of imaginary frequencies in chemical reaction rates and molecular liquids

Abstract: A simple model is presented for treating local imaginary frequencies that are important in the study of quantum effects in chemical reactions and various dynamical processes in molecular liquids. It significantly extends the range of accuracy of conventional local harmonic approximations (LHAs) used in the linearized semiclassical initial value representation/classical Wigner approximation for real time correlation functions. The key idea is realizing that a local Gaussian approximation (LGA) for the momentum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 63 publications
2
111
0
Order By: Relevance
“…(A5) corresponds to the case of the non-equilibrium Kubo-transformed correlation functionC AB (t) from Eqs. (12)- (14). There is currently no general transformation between Kubo-transformed nonequilibrium TCFs and standard non-equilibrium TCFs.…”
Section: Appendix A: Connection To Condon Approximationmentioning
confidence: 99%
“…(A5) corresponds to the case of the non-equilibrium Kubo-transformed correlation functionC AB (t) from Eqs. (12)- (14). There is currently no general transformation between Kubo-transformed nonequilibrium TCFs and standard non-equilibrium TCFs.…”
Section: Appendix A: Connection To Condon Approximationmentioning
confidence: 99%
“…The LSC-IVR retains the Boltzmann quantum statistics inside a Wigner transform, 26 is exact in the zero-time, harmonic and high-temperature limits, and has been developed into a practical method by several authors. [19][20][21][22][23] However, it has a serious drawback: the classical dynamics does not in general preserve the quantum Boltzmann distribution, and thus the quality of the statistics deteriorates over time.…”
Section: Introductionmentioning
confidence: 99%
“…für Physikalische Chemie, ETH Zürich, CH-8093 Zürich, Switzerland b) Corresponding author: sca10@cam.ac.uk approximation), 3,[15][16][17][18][19][20][21][22][23][24][25][26][27] in which the quantum Liouvillian is expanded as a power series in 2 , then truncated at 0 . Miller 15,16 and later Shi and Geva 17 showed that this approximation is equivalent to linearizing the displacement between forward and backward Feynman paths in the exact quantum time-propagation, which removes the coherences, thus making the dynamics classical.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28]54 In this approach, Feynman paths in the forward and backward real-time propagators are assumed to cancel out unless they are very close together, such that the difference in their actions can be expanded to linear order in position. This approximation has the effect of removing all real-time Feynman paths, except the forwardbackward pairs that lie along classical trajectories joining the start and end points, which reduces the timecorrelation function to its classical Wigner approximation.…”
Section: Introductionmentioning
confidence: 99%
“…* Corresponding author: sca10@cam.ac.uk most famous instance of this being the Wigner-Eyring formula. 13 A more systematic approach is to use semiclassical theories [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (some of which we discuss below), or the quantum instanton approach. 29,30 However, there is one approach 20,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] that is especially relevant to this article, which is to note that classical TST takes the form of a free-energy combined with a flux factor, and then to exploit the fact that it is relatively easy to compute a quantum free energy, using 'ring-polymer' pathintegration.…”
Section: Introductionmentioning
confidence: 99%